PENGARUH SKEPTISME, PENGALAMAN AUDITOR DAN SELF EFFICACY TERHADAP AUDIT JUDGMENT (Studi Empiris pada Auditor Badan Pengawasan Keuangan dan Pembangunan (BPKP) Perwakilan Provinsi Bengkulu) - Wiwien Maryani; Fitrawati Ilyas (Jurnal Akuntansi, 2017)
This study aimed to examine the effect of skepticism, the experience of auditors, and self-efficacy on audit judgment. This research used primary data obtained by distributing questionnaires to the auditors who worked at BPKP Bengkulu province. The sample was selected using a purposive sampling method. 60 questionnaires were distributed to respondents (sample), but only 52 questionnaires that can be analyzed or processed. The study used Multiple Regression Analysis. The results showed that skepticism, the experience of auditors and self-efficacy has a positive influence on audit judgment. The results of this study are expected to be taken into consideration for the representative offices Financial and Development Supervisory Agency (BPKP) Bengkulu Province to give more attention about the importance of skepticism, the experience of auditors and self-efficacy affecting the audit judgment.Keywords: Skepticism, experience of auditor, self efficacy, and audit judgment.